2020
DOI: 10.1111/nmo.13803
|View full text |Cite
|
Sign up to set email alerts
|

D‐methionine improves cisplatin‐induced anorexia and dyspepsia syndrome by attenuating intestinal tryptophan hydroxylase 1 activity and increasing plasma leptin concentration

Abstract: Background:Cisplatin is a widely used antineoplastic drug. However, cisplatin-induced dyspepsia syndromes, including delayed gastric emptying, gastric distension, early satiety, nausea, and vomiting, often force patients to take doses lower than those prescribed or even refuse treatment. D-methionine has an appetite-enhancing effect and alleviates weight loss during cisplatin treatment. Methods:This work established a model of anorexia and dyspepsia symptoms with intraperitoneal injection of cisplatin (5 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(75 reference statements)
0
4
0
1
Order By: Relevance
“…Patients with hepatic fibrosis had a higher abundance of the Escherichia-Shigella and Enterobacteriaceae families [ 58 ]. Additionally, CKD patients showed higher levels of Enterobacteriaceae but lower levels of Ruminococcaceae compared with the healthy individuals [ 59 ]. Consistent with previous research, our results showed that cisplatin disturbed the intestinal microbiota that exacerbated mucosal damage [ 1 ] and kidney damage [ 2 , 19 ] and induced Escherichia-Shigella as the dominant genera [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hepatic fibrosis had a higher abundance of the Escherichia-Shigella and Enterobacteriaceae families [ 58 ]. Additionally, CKD patients showed higher levels of Enterobacteriaceae but lower levels of Ruminococcaceae compared with the healthy individuals [ 59 ]. Consistent with previous research, our results showed that cisplatin disturbed the intestinal microbiota that exacerbated mucosal damage [ 1 ] and kidney damage [ 2 , 19 ] and induced Escherichia-Shigella as the dominant genera [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy may affect gastrointestinal motility, as well as that of neurotransmitters. It was reported that the delayed gastric emptying caused by chemotherapy may also be an important factor in explaining CINV [ 48 , 49 , 50 ]. The gingerols in ginger markedly improved delayed gastric emptying induced by cisplatin in a dose-dependent manner [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common side effects of platinum-based chemotherapeutic drugs is weight loss (44)(45)(46). There have been many mechanisms proposed for how cisplatin and other platinum-based chemotherapeutic drugs cause weight loss (69)(70)(71)(72)(73)(74)(75)(76). Meclizine reduced both cisplatin-induced hypersensitivity to mechanical pain and attenuated cisplatin-induced weight loss.…”
Section: Discussionmentioning
confidence: 99%